2011
DOI: 10.1128/aac.00709-10
|View full text |Cite
|
Sign up to set email alerts
|

Novel Compounds Containing Multiple Guanide Groups That Bind the HIV Coreceptor CXCR4

Abstract: The G-protein-coupled receptor CXCR4 acts as a coreceptor for human immunodeficiency virus type 1 (HIV-1) infection, as well as being involved in signaling cell migration and proliferation. Compounds that block CXCR4 interactions have potential uses as HIV entry inhibitors to complement drugs such as maraviroc that block the alternate coreceptor CCR5 or in cancer therapy. The peptide T140, which contains five arginine residues, is the most potent antagonist of CXCR4 developed to date. In a search for nonpeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…The TOAM guanide derivatives were synthesized as described previously for the corresponding THAM compounds [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TOAM guanide derivatives were synthesized as described previously for the corresponding THAM compounds [4].…”
Section: Methodsmentioning
confidence: 99%
“…Some of these compounds were previously found to be effective as antagonists of CXCR4 and inhibited HIV infection by X4 strains [4], [5] and the formation of metastatic tumors [6]. The biguanide series of compounds are chemically related to some commercially important biocidal agents found in common household items such as disinfectants, mouthwashes, contact lens solutions, and cosmetics.…”
Section: Introductionmentioning
confidence: 99%
“…Small molecules containing multiple guanide or biguanide groups are capable of inhibiting HIV-1 binding to CXCR4 100. In particular, an oligomer based on a biguanide moiety, NB325, showed wide antiviral activity in several in vitro assays.…”
Section: Guanidine-based Cxcr4 Antagonistsmentioning
confidence: 99%
“…However, since such preparation consists of a variable mixture of compounds containing from 4 to 10 biguanide groups, endowed with intractable activities, its development will be challenging. This study therefore focused on the design and development of a series of single small molecules containing multiple guanide or biguanide groups ( Table 2, Figure 20 ) 100. These compounds include some features of the polyethylene-hexamethylene biguanide NB325, as well as the peptide T140 that has five guanide groups on the side chains of arginine residues.…”
Section: Guanidine-based Cxcr4 Antagonistsmentioning
confidence: 99%
“…This T140 derivative has been reported to crosslink to CXCR4 and serves as a positive control (18). We also demonstrated that FL-T140-BzF crosslinks specifically to CXCR4 in cell culture.…”
mentioning
confidence: 99%